Effect of Implementation Technological Enchanced Learning in Physical Fitness Material on Student Learning Motivation - Wili Rafiandi; Asep Sumpena; Burhan Hambali (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study presents an analysis of the effect of the application of Technological Enhanced Learning (TEL) in physical fitness material on student learning motivation at Junior High School 3 Cileunyi. The research design used was a one-shot case study with a control group, involving 40 students who were divided into experimental and control groups. The instrument used was a questionnaire to measure students' learning motivation, including aspects of interest, involvement, and drive to learn. The results showed a significant increase in the learning motivation of students who participated in technology-based learning compared to the control group, who used conventional methods. Statistical analysis using the independent T-test indicated that the application of TEL can positively influence students' learning motivation. The findings support the theory that interactive learning experiences can increase student motivation, as well as making an important contribution to the development of pedagogy in physical education. This study recommends the use of technology as an innovative solution to improve student engagement and learning quality in physical fitness materials. Future research is recommended to expand the research sample to provide a clearer picture of the effectiveness of TEL.